Use of Maps for Socio-Economics Studies with Reference to Malaysia - Voon, Phin Keong (INTI Publishing House Sdn Bhd, 2005)
Maps are intellectual devices that are essential for reference and research. They are indispensable for showing spatial data and non-verbal information. This paper discusses the role of maps in socio-economic studies and research with reference to selected Malaysian examples. These examples include research on settlements based on topographic maps, the use of cadastral maps for studies relating to land parcels, and maps as illustrative devices. The prospects and possibilities of maps for research arising from advancement towards the digital format are also examined.